2021
DOI: 10.3389/fpubh.2021.653931
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Older Adults' World: Concepts of Aging, Care, and Using Assistive Technology in Late Adulthood

Abstract: The ongoing demographic change forces different stakeholders to cope with increasing needs in nursing care and the economic costs. Consequences arising from the population aging can be supported by assistive technologies to maintain older individuals' autonomy. However, older adults' opinions on the assistance of health-related technologies and their attitudes toward aging and care largely remain underexplored. This paper provides a geriatric and socio-technical perspective, investigating individual perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…The results of this study showed that 149 (70.6%) of the Tibetan seniors had the willingness to use ADs, and this data set also indicated that the willingness of seniors to accept ADs is universal, which is consistent with the study by Wilkowska et al 35 The reasons for this are mainly related to the functional decline in the elderly and the need for ADs to maintain their basic self-care ability. China’s population is developing from a pyramid to an inverted pyramid, and the “421 family model” (ie, 2 adults will be responsible for supporting 4 seniors and 1 child) has become the basic family structure in China, and the burden of pension is getting heavier.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study showed that 149 (70.6%) of the Tibetan seniors had the willingness to use ADs, and this data set also indicated that the willingness of seniors to accept ADs is universal, which is consistent with the study by Wilkowska et al 35 The reasons for this are mainly related to the functional decline in the elderly and the need for ADs to maintain their basic self-care ability. China’s population is developing from a pyramid to an inverted pyramid, and the “421 family model” (ie, 2 adults will be responsible for supporting 4 seniors and 1 child) has become the basic family structure in China, and the burden of pension is getting heavier.…”
Section: Discussionsupporting
confidence: 90%
“…As more and more technologies emerge to assist older adults, researchers should consider the effect of health-related technologies on the people being monitored [11]. Most people want to keep their health information private, and they also worry about how such information could be used against them.…”
Section: Vision Sensor-based Recognition Systemsmentioning
confidence: 99%
“…Most people want to keep their health information private, and they also worry about how such information could be used against them. According to surveys collected by the authors in [11], older adults have positive opinions of assistive technologies, but rarely accept systems that use cameras because of privacy concerns. To overcome this attitude, the use of depth cameras became more common for their advantages from a privacy perspective.…”
Section: Vision Sensor-based Recognition Systemsmentioning
confidence: 99%
“…15 Assistive technology is a term for systems or services that promote independence and improve function. 16 It encompasses a wide range of products from "low-technology" items, such as grab bars, walkers, and reminder calendars, to "high-technology" items, such as sensors, remote monitoring systems, and GPS tracking technology. 17 While many studies focus on the use of assistive technology for persons with disabilities, researchers globally and organizations like the World Health Organization have expanded the scope to include older people and people experiencing gradual functional decline.…”
mentioning
confidence: 99%
“… 15 Assistive technology is a term for systems or services that promote independence and improve function. 16 It encompasses a wide range of products from “low-technology” items, such as grab bars, walkers, and reminder calendars, to “high-technology” items, such as sensors, remote monitoring systems, and GPS tracking technology. 17…”
mentioning
confidence: 99%